Hubungan Kreativitas Berpikir Siswa dengan Prestasi Belajar Siswa di Kelas 7 SMPIT Ummul Aminah Kota Depok - Nanda Nasvia; Chodidjah Makarim; Andesten Andesten (Tarbiatuna: Journal of Islamic Education Studies, 2024)
There are still students at SMPIT Ummul Aminah Depok City who lack student thinking creativity, in this case, the need for motivation from teachers in educating and guiding students to grow and get Islamic Religious Education learning achievements, so that the better the creativity of students' thinking, the higher the students' Islamic Education learning achievements. The objectives of this study are: (1) to find out how PAI learning achievement in class VII SMPIT Ummul Aminah Depok City, (2) to find out the factors inhibiting PAI learning achievement of students in grade VII SMPIT Ummul Aminah Depok City, (3) to find out how the level of creativity of students thinking in grade VII SMPIT Ummul Aminah Depok City, (4) to find out how teacher efforts to increase the creativity of students in grade VII SMPIT Ummul Aminah Depok City, (5) to find out whether there is a significant relationship between students' thinking creativity and Islamic Education learning achievement in class VII SMPIT Ummul Aminah Depok City. The data collection technique used is a questionnaire with a correlation method. The results of this study show that: (1) students' Islamic Religious Education learning achievement is included in the very good category, (2) factors inhibiting students' Islamic Education learning achievement in grade VII SMPIT Ummul Aminah Depok City are lack of motivation from the students themselves to study harder, (3) variable X statement (student thinking creativity) most students answer in the affirmative and based on the variable category that students' thinking creativity is in the good category, (4) teachers' efforts for student creativity are to provide motivation to students, (5) there is a significant relationship between students' thinking creativity and students' Islamic Education learning achievement is included in the medium category.